"I Don't Know Everything, But Ethan Would Know": Language, Expertise, and the Cultural Mismatch for Women Scientists. Issue 1 (2nd January 2017) - Hirshfield, Laura Ellen
Abstract : Using participant observation and interview data, the author explores interactional styles that men and women chemists-in-training (graduate students and postdoctoral fellows) use to navigate expertise within their research groups. The author finds that men are more likely than women to employ styles that feature their expertise when in group situations, while women are more likely to minimize theirs. Specifically, the author discusses peer-to-peer challenges and gender differences in self-deprecating comments, as well as the consequences of these tactics for success in the natural sciences.